TINJAUAN ATAS KEBUTUHAN LP KHUSUS BAGI NARAPIDANA KASUS KORUPSI DI INDONESIA - F.H. Edy Nugroho (Faculty of Law, Universitas Diponegoro, 2015)
This article aims to study the necessity of special rehabilitation institutes for criminals of corruption cases. The placement for criminals of corruption cases in a special prisons (a rehabilitation institute) is a development punisment in Indonesia. It is very important because they have special characteristics. They also need special guidance and supervision different with the others criminals. The development of special rehabilitation institutes for them make control and supervision more easily than usual. It will accomplish the goals of punishment for them. It will give sense of justice to society too.